ANATOMI DAN IDENTIFIKASI KAYU KAPUR (Dryobalanops) (ANATOMY AND IDENTIFICATION OF KAPUR (Dryobalanops) WOOD) - Nenny S Sudarna (Jurnal Penelitian Hasil Hutan, 1993)
The anatomy of 9 wood species belonging to genera of Dryobalanops was studied, described and then compared. Dryobalanops rappa Becc differ from others in the absence of silica body in rays cell.Although the morphology of D. oocarpa V.SI. and D. abnormes V.SI. respectively can be grouped to D. beccarii Dyer and D. oblongifolia Dyer, but the anatomy of those wood species differ from each other. Whereas D. oocarpa V.SI. has rays 2 - 5 seriate-in width and 79.84 + 0.23 micron in diameter, D. beccarii Dyer has rays 1 - 3 seriate in width and 51.94 ± 0.12 micron in diameter. D. abnormes V.Sl. has rays 1 - 3 seriate in width and 53.68 + 0.20 micron in diameter, D. oblongifolia Dyer has rays 2. - 5 seriate in width and 76.89 + 0.23 micron in diameter.A tentative identification key of 9 wood species of Dryobalanops is presented.